The relation between performance and oral health in male athletes - Yapıcı, Hakan; Eroğlu, Oğuz; Ayan, Sinan; Bağlar, Serdar; Memiş, Uğur Altay; Doğan, Ali Ahmet (The European Research Journal, 2019)
Objectives: Oral health is as important to an athlete’s sporting successas regular exercise and adequate nutrition. The aim of this study was to investigate the relation between oral health and sporting performance.Methods: This prospective study was carried out with male athletes. Athletes' demographic characteristics, dental care habits, number of decayed, missing or filled teeth, and sporting performance data were recorded. The Decayed Missing Filled Teeth (DMFT) index, Significant Caries index (SCI) and Plaque index (PI) were used to assess oral health. The T-Drill, Zig-Zag, Lateral Change of Direction (LCD) and 505 tests to assess agility, and 10-, 20- and 30-m short sprint tests were used to assess speed. The results were analyzed on SPSS software, and p values < 0.05 were regarded as significant.Results: Ninety-six athletes were included in the study. Active caries was determined in 70.8%. The mean DMFT index value was 3.9 ± 3.7, mean SCI 10.2, and mean PI 0.9 ± 0.4. DMFT was  ≥ 4 in 45.8% of athletes and < 4 in 57.2%. No difference was determined between subjects with DMFT < 4 and DMFT ≥ 4 in terms of age, height, body weight, or years engaged in sports. Agility and speed tests results were superior in subjects with DMFT